1981
DOI: 10.1098/rstb.1981.0029
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of higher thought 3.0-0.2 Ma B . P

Abstract: The oldest known probable manuport is the dark reddish jasperite pebble from a layer with Australopithecus at Makapansgat, Transvaal ( ca . 3 Ma). There are indications at two earliest Acheulian sites in east Africa that Homo erectus ol ca . 1.5 Ma B . P .was interested in red mineral pigment. At Terra Amata,near Nice, 75 shaped pieces of red ochre were found with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Analysis of Acheulean hand-axe assemblages made 300,000 years ago suggests that their makers were fully capable of operational thought (117), which might imply that changes in general level of intelligence were not a factor in later developments . There is also evidence for an aesthetic and symbolic sense at about this time or earlier among Homo erectus populations (55,85). However, the time structures implied by the flaking of a hand-axe are not necessarily the same as those implied by human burial or representational art .…”
Section: Prehistoric Time Structuresmentioning
confidence: 95%
“…Analysis of Acheulean hand-axe assemblages made 300,000 years ago suggests that their makers were fully capable of operational thought (117), which might imply that changes in general level of intelligence were not a factor in later developments . There is also evidence for an aesthetic and symbolic sense at about this time or earlier among Homo erectus populations (55,85). However, the time structures implied by the flaking of a hand-axe are not necessarily the same as those implied by human burial or representational art .…”
Section: Prehistoric Time Structuresmentioning
confidence: 95%
“…Its red colour alone would be striking in almost any environment but more particularly so in combination with its distinctive shape. Oakley (1981) emphasised the role of red colour for hominids. But it does not seem likely that it would have been picked up and carried for some considerable distance just for these properties and by far the most conspicuous aspects of this object are its menacing 'eyes' as well as several other, very prominent markings, all of which underline the iconographic properties and make it resemble a face.…”
Section: Discussionmentioning
confidence: 99%
“…Upon re-examining it in the early 1970s he noticed that, depending on how it is held and lit, several 'faces' can be seen, resembling australopithecines rather than humans (Dart 1974). The object has been briefly discussed by Oakley (1981) and featured in two British television programs, and was thus presented as the oldest apparent 'art find' known to us. Balm examined it in 1996 and reported its history since its excavation (Bahn 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, examination of the object shows that the grooves are of a purely geological nature. Another hand-axe, this one from the Lower Paleolithic of West Tofts, Norfolk, Britain (Oakley 1981) [137], bears a distinctive fossil cast of a shell on one face. It has been suggested that the tool was intentionally knapped around the prominent fossil, in which case it would not necessarily be symbolic, but would be exogrammatic.…”
Section: Lower Paleolithic Paleoartmentioning
confidence: 99%